Effect of different levels of urea added to a mineral salt mixture upon the intake and digestibility of two tropical grass hays - Silva, José Marques da; Thiago, Luiz Roberto Lopes de S.; Cardoso, Esther Guimarães (Pesquisa Agropecuaria Brasileira, 2014)
The effect of urea suplementation on intake and digestibility of jaraguá grass (Hyparrhenia rufa (Ness), Stapf.) and Brachiaria grass (Brachiariaruziensis, Germain & Evrard) hays was studied with 25 Nelore (Zebu) steers in a completely randomized design. Steers were housed in individual pens where they received free choice the treatments consisting of mineral mix plus zero, 20%, 40%, 60% or 80% urea in two trials of 56 and 49 days. Dry matter, organic matter, acid detergent fiber and gross energy digestibility remained the same for all treatments. Crude protein intake, protein digestibility as well as nitrogen retention were increased in the urea supplemented groups as compared to controls. Dry matter, digestible organic matter and metabolizable energy intakes from jaraguá hay (5,3% CP) increased in the urea supplemented groups but no such effect was observed with Brachiaria hay (8,4% CP).